Influence of Virtue Ethics on Counselling Morale Application amongst Trainee Counsellors who undergo Internship - Nor Mazlina, Ghazali; Nor Aisha, Mustafa; Wan Marzuki, Wan Jaafar; Azzahrah, Anuar; Lee, May Fern (National Taiwan Normal University, 2017)
The nature of virtue ethics is important in counselling process. The investigation on virtue ethics (benevolence and respectfulness) is on counselling morale application among trainee counsellors. Purposes of this research are (i) to investigate the relationship between “benevolence” and different culture among trainee counsellors. (ii) to investigate the relationship between “respectfulness” and different culture among trainee counsellors, (iii) to investigate the relationship between cultural differences and morale application among trainee counsellors and (iv) to investigate the use of “benevolence” and morale application among trainee counsellors. Instruments used to measure the variables are Schwartz Value Survey (SVS), Multicultural Attitude Scale (MAS) and Vision of Morality Scale (VMS). Finding showed the virtue ethics (benevolence and respectfulness) on counselling morale application. As summary the virtue ethics is important in making decision among counsellors in counselling process.